2007
DOI: 10.1161/strokeaha.106.480863
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombotic Mutations as Risk Factors for Cryptogenic Ischemic Cerebrovascular Events in Young Subjects With Patent Foramen Ovale

Abstract: Background and Purpose-Patent foramen ovale (PFO) has been identified as a potential risk factor for cerebrovascular ischemia. Procoagulant mutations may increase the risk and impact the choice of appropriate therapy for secondary prevention. We evaluated the prevalence of the 2 most common genetic risk factors for thromboembolism, factor V Leiden (G1691A) and prothrombin G20210A, in young PFO patients who were referred for percutaneous transcatheter closure of their PFO. Methods-Ninety-seven patients (50 men;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
2
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 23 publications
2
50
2
3
Order By: Relevance
“…An example of well-defined potentiation is seen among women with migraine as relative stroke risk of migraine is strongly increased by oral contraceptive use and smoking. 21 PFO, with or without ASA, and its association with migraine 22 or prothrombotic mutations 23 demonstrates another complex interaction of factors with low primary risk alone. However, PFO with or without ASA, or ASA alone, should be considered as potential sources of cardioembolism in young adults-despite the difficulties of confirming the paradoxical embolism, in situ thrombosis, or transient atrial arrythmia.…”
Section: Putaala Et Al Features Of Ischemic Stroke In the Young 1199mentioning
confidence: 99%
“…An example of well-defined potentiation is seen among women with migraine as relative stroke risk of migraine is strongly increased by oral contraceptive use and smoking. 21 PFO, with or without ASA, and its association with migraine 22 or prothrombotic mutations 23 demonstrates another complex interaction of factors with low primary risk alone. However, PFO with or without ASA, or ASA alone, should be considered as potential sources of cardioembolism in young adults-despite the difficulties of confirming the paradoxical embolism, in situ thrombosis, or transient atrial arrythmia.…”
Section: Putaala Et Al Features Of Ischemic Stroke In the Young 1199mentioning
confidence: 99%
“…5 In a relatively large study of prothrombotic gene mutations, Berge et al 6 found a small, nonsignificantly higher risk of early recurrent ischemic cerebrovascular events among patients who were carriers of the Factor V Leiden mutation. Botto et al 7 found increased prevalence of at least one prothrombotic genotype among patients with patent foramen ovale and first-ever ischemic cerebrovascular event before the age of 55 years. In fact, a combination of Factor V Leiden mutation or prothrombin gene mutation and patent foramen ovale was associated with a 4.7-fold increased risk for ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…A cumulative effect of factor V Leiden or prothrombin gene (G20210A) mutations and the presence of PFO for the occurrence of cerebral circulation disorders is emphasized. In the studies of Botto et al and Pezzini et al these mutations occurred significantly more often in patients with stroke and PFO as compared to healthy individuals [19,20]. Coagulation disorders in young patients with stroke are of minor importance, which however increases with the presence of other pathologies, such as PFO.…”
Section: Patent Foramen Ovalementioning
confidence: 94%